The monitoring of the infection of the rodents by helminthes in the delta of the Volga - V. V. Fedorovich; A. P. Kalmykov; V. M. Ivanov; N. N. Semyonova; O. Y. Parshina (Юг России: экология, развитие, 2015)
Perennial data about the infection of the rodents by helminthes in the delta of the Volga have been received. The indexes of the dynamics of the animals’ infection by the trematodes Alaria alata, Conodiplostostomum spathula, Plagiorchis arvicolae, by the cestode Mesocestoides lineatus and by the nematode Syphacia obvelata have been adduced. There have been found out, that changes of the infection of the rodents by helminthes are from the natural and anthropogenic factors. These factors are the introduction of the animals, the instability of the hydrologic mode in the Volga delta, the number and the allocation of the intervening hosts.